Notes on the genus Libellulosoma Martin, 1906, and related genera (Odonata: Anisoptera: Corduliidae) - Fleck, Günther; Legrand, Jean (Zootaxa, 2013)
The holotype of Libellulosoma minuta, until now regarded as the unique specimen of this monotypic genus and considered lost for half a century, was found again in the dragonfly collection of the Muséum National d’Histoire Naturelle in Paris. A second specimen, also from Madagascar (probably East Madagascar) was found in the collection René Martin together with the holotype. A redescription, including the structure of the secondary copulatory apparatus, is provided. The genus Libellulosoma is closely related to the genera Pentathemis and Aeschnosoma, and its membership in the clade Aeschnosomata is well supported. Evidence from biogeography, the fossil record, and phylogeny indicates that this group, possible sister group of remaining Corduliidae s.s., was probably already present in the Early Cretaceous.